Governance for sustainable development : a foundation for the future - Ayre, Georgina; Callway, Rosalie (Earthscan, 2005)
As the process of globalization continues and power imbalances between decision-making institutions become increasingly apparent the need for a critical assessment of the way in which we manage our interaction with the natural environment becomes ever more urgent. Good governance was identified at the World Summit on Sustainable Development as a critical factor for ensuring successful sustainable development. This book builds on the briefing papers that were presented at the Summit taking further the discussions of the WEHAB agenda (Water Energy Health Agriculture and food and Biodiversity - t.